Calidad del cuidado de enfermería y el nivel de satisfacción del usuario adulto mayor. Servicio de hospitalización medicina. Hospital II-2 MINSA Tarapoto. Agosto- Diciembre 2011 - Altamirano Requejo, Nancy (2012)
This study entitled "Nursing Care Quality and User Satisfaction Level Servicio Senior Hospital Medical Hospital II-2 MINSA Tarapoto. August- December 2011", aimed to: Determine the relations hipbetween the quality of nursing care and the level of user satisfaction elderly Medicina del Area Hospital Hospital II-2 MINSA Tarapoto, in the same way was raised Identify the quality of nursing care that is provided in the medical service of this institution, and the level of user satisfaction with respect toelderly nursing care receivedin the service e and ultimately identify the dimension of nursing care greater satisfaction withol deruserperceives Servicio Hospital Medical Hospital II-2 MINSA Tarapoto. The research is quantitative aqualitative approachis developed under the descriptive designas a strategyto determinethe relation shipbetween the quality ofnursing careand the level ofuser satisfactionelderlyto measure qualityof nursing caretechniquewas used asan instrumentof observation andthe checklistto measurethe level ofuser satisfactionwas used as adatacollection techniqueand an instrument surveyquestionnaire,the constructs ofboth instruments were validated by Expert Judgement. To interpretand analyze the behaviorof the variablesunder study and also of the otherfeatures, such asdemographicdescriptive statisticswere used. The sampleconsisted of 07 nurses and 20 patients Area Senior Hospital MedicalHospitalII-2 MINSA Tarapoto.August to December 2011. The findingsin this studywere thatboth thequalityof nursing careanduser satisfaction level elderly is high quality effective nursing carehighly influencesthe level ofuser satisfaction Hospital Servicio Hospital medicineII-2 MINSA Tarapoto so there isa direct relationship.